Self-Efficacy to Make Health Behaviour Changes: A Survey of Older Adults Living in Ontario Social Housing - Dias, Hanna; Brar, Jasdeep; Keenan, Amelia; Sadri, Pauneez; Pirrie, Melissa; Angeles, Ric; Marzanek, Francine; Koester, Christie; Plishka, Mikayla; Dzerounian, Jasmine; AlShenaiber, Leena; Agarwal, Gina (My University, 2022)
A cross-sectional survey with adults ages 55+ (n=599) from 16 social housing buildings across five Ontario communities used the Health Awareness and Behaviour Tool (HABiT) to measure participants' self efficacy (or confidence) for health behaviour change.
Keywords: Primary Care; Social Housing; Vulnerable Populations; Health Behaviour